RÖSNITZ/ROZUMICE. POLIFONICZNOŚĆ GÓRNOŚLĄSKIEJ TRADYCJI PROTESTANCKIEJ - Gładkowski, Krzysztof (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The author presents here the detailed results of his research on the religious past of the Lutheran community of Rösnitz (today’s Polish name Rozumice) in Upper Silesia. This village is situated on the border with today’s Czech Republic. Today it is a place of remembrance of the continuity of Protestant tradition, including pre-reform movements, since the 15th century. The continuity of the Lutheran denomination of the community since 1523 of the, which the author’s research has shown, contradicts the generalized thesis of total recatholization of Upper Silesia. This article highlights one issue of the memorial site – the diversity of the Protestant tradition shown by the research of the past of this Lutheran community. This diverse tradition consists of pre-reformation Christian movements, including the Moravian Brothers, with whom the inhabitants of Rösnitz had already established contacts before the end of the 15th century. In the beliefs of this community, there are also themes characteristic for Waldensians who were known in Silesia. These movements prepared Rösnitz dwellers for the acceptance of Lutheranism. During the counterreformation period, the community did not undergo a recatholization. Later, Pietism strongly influenced the area, Count Ludwik von Zinzendof himself visits Rösnitz, where he speaks to the many gathered there from the surrounding villages. It even came to a split in this so far united municipality, which resulted in the emmigration of followers of Unita Fratrum to Herrnhut.